(untitled) (Annals of Medical Research, 2023)
Aim: Dermatomycoses are superficial fungal infections of the skin, hair and nails. The fungi responsible for dermatomycoses include dermatophytes, yeasts and non-dermatophytic molds (NDM). Onychomycosis is the most common nail disease caused by dermatophytes, NDMs, and yeasts with a worldwide. This study was under taken to investigate the current distribution of aetiological agents of dermatomycoses. Materials and Methods: In this study, we evaluated the microscopic examination and culture results of the samples taken from the patients who applied to our clinic for two year. Species were identification on the basis of combined clinical pictures, culture and microscopic morphology characters of together. Results: During the study period, 592 samples were examined. The distribution of isolates was found to be 47.2% (n=118) NDM, 26.4% (66) dermatophytes and 26.4% (66) yeasts, respectively. Tinea unguium was the most prevalent type of dermatophytoses. Trichophyton rubrum was most frequent aetiological agents of detected in patients. According to our study, 22% of non-dermatophyte hyaline molds are Fusarium spp. and 21% are Aspergillus spp. species. Conclusion: Several studies have shown that both the prevalence and aetiology of dermatomycoses can change according to geographical location, climatic conditions, and personal factors. The objective of our study was to analyse 2 years of epidemiological data regarding dermatological mycology testing performed in a large tertiary care teaching hospital in Eskişehir, This report represents the most comprehensive analysis of this type from Eskişehir, and it is hoped that its findings will be of interest to, and inform, researchers and clinicians focused on mycoses and international epidemiology. To the best of our knowledge, we provide the first analysis from Eskisehir of fungal detections from all external body site (skin, hair and nail).